Market Integration and Price Execution for NYSE-Listed Securities. - Lee, Charles M C (Journal of Finance, 1993)
For New York Stock Exchange listed securities, the price execution of seemingly comparable orders differs systematically by location. In general, executions at the Cincinnati, Midwest, and New York stock exchanges are most favorable to trade initiators, while executions at the National Association of Security Dealers are least favorable. These intermarket price differences depend on trade size, with the smallest trades exhibiting the biggest per share price difference. Collectively, these results raise questions about the adequacy of the existing intermarket quote system, the broker's fiduciary responsibility for 'best execution,'and the propriety of order flow inducements.